The Influence of Purchase Price and Ownership Levels on Theft Targets: The Example - Wellsmith, Melanie (The British journal of criminology, 2005)
In this paper, we use police recorded crime data and purchase price information to investigate patterns in property stolen during domestic burglaries. We test the hypotheses that frequently stolen items are CRAVED' (Clarke 1999) and that the levels at which items are stolen vary over time, according to a product's position in the consumer goods life cycle of innovation, growth, mass market, saturation (Felson and Clarke 1998). We focus on audio-visual equipment and mobile telephones, comparing the trends with those for cash. The results show that the prevalence of theft of the products considered has changed significantly over the period studied, consistent with the life cycle hypothesis. The crime prevention implications of these findings are discussed and suggestions for further research considered